BI1 alleviates cardiac microvascular ischemia‐reperfusion injury via modifying mitochondrial fission and inhibiting XO/ROS/F‐actin pathways. Issue 4 (7th September 2018) - Zhou, Hao; Wang, Jin; Hu, Shunying; Zhu, Hong; Toan, Sam; Ren, Jun
Abstract: Pathogenesis of cardiac microvascular ischemia‐reperfusion (IR) injury is associated with excessive mitochondrial fission. However, the upstream mediator of mitochondrial fission remains obscure. Bax inhibitor 1 (BI1) is linked to multiple mitochondrial functions, and there have been no studies investigating the contribution of BI1 on mitochondrial fission in the setting of cardiac microvascular IR injury. This study was undertaken to establish the action of BI1 on the cardiac microvascular reperfusion injury and figure out whether BI1 sustained endothelial viability via inhibiting mitochondrial fission. Our observation indicated that BI1 was downregulated in reperfused hearts and overexpression of BI1 attenuated microvascular IR injury. Mechanistically, reperfusion injury elevated the levels of xanthine oxidase (XO), an effect that was followed by increased reactive oxygen species (ROS) production. Subsequently, oxidative stress mediated F‐actin depolymerization and the latter promoted mitochondrial fission. Aberrant fission caused mitochondrial dysfunction and ultimately activated mitochondrial apoptosis in cardiac microvascular endothelial cells. By comparison, BI1 overexpression repressed XO expression and thus neutralized ROS, interrupting F‐actin‐mediated mitochondrial fission. The inhibitory effect of BI1 on mitochondrial fission sustained endothelial viability, reversed endothelial barrier integrity, attenuated the microvascular inflammation response, and maintained microcirculation patency. Altogether, we conclude that BI1 is essential in maintaining mitochondrial homeostasis and alleviating cardiac microvascular IR injury. Deregulated BI1 via the XO/ROS/F‐actin pathways plays a causative role in the development of cardiac microvascular reperfusion injury. Abstract : We conclude that Bax inhibitor 1 (BI1) is essential in maintaining mitochondrial homeostasis and alleviating cardiac microvascular ischemia‐reperfusion injury. Deregulated BI1 via the xanthine oxidase/reactive oxygen species/F‐actin pathways plays a causative role in the development of cardiac microvascular reperfusion injury.